Pengembangan Asesmen Diagnostik Kognitif pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di Sekolah Dasar Kurikulum Merdeka - Aslihah Aslihah; Enung Nugraha; Fitri Hilmiyati (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The Merdeka Belajar program focuses on authentic assessments that reflect students' factual knowledge, focusing on written assessments and students' abilities to apply and adapt the concepts learned in everyday life. The goal of the program's cognitive diagnostic assessment is to diagnose students' core skills and assess their baseline status. Emphasizing diagnostic assessments allows students to reflect on their thinking, identify their strengths, and assess their weaknesses. A qualitative approach was used in this research by utilizing sources related to cognitive diagnostic research, religious education, and Islam. Diagnostic assessments in Islamic religious and character education subjects in elementary schools, especially in the elements of aqidah in grades 3, 4 and 5, aim to achieve the same learning objectives, namely providing information and material related to Asmaul Husna to students. The development of this diagnostic assessment should be able to be adjusted to the differences in students' abilities in the class, so that teachers can determine teaching methods and work formats that suit individual students' abilities.